La lirica di Vasyl' Stus Modernismo e intertestualità poetica nell'Ucraina del secondo Novecento - Achilli, Alessandro (Biblioteca di Studi Slavistici, 2018)
Vasyl' Stus's (1938-1985) poetry is one of the richest and most complex chapters in the literary history of late Soviet Ukraine. His poems are not only born of the author's talent, but also of his erudition and deep cultural awareness; Stus's poetry eloquently shows the presence of a significant Modernist trend in the literature of the Ukrainian underground during the Age of Economic stagnation. Stus's Modernism is the ideal evolution of the Ukrainian poetic culture of the first decades of the century, and develops thanks to an intense intertextual dialogue with the European literature. Stus's reception of Russian and German poetry, in addition to becoming the model for nineteenth-century and early-twentieth-century Ukrainian poetry, proves fundamental to fully understand his work's literary palimpsest, which this volume offers a comprehensive reading of, from the early stages to the maturity's collections.